Alginate-based microparticles coated with HPMCP/AS cellulose-derivatives enable the Ctx(Ile21)-Ha antimicrobial peptide application as a feed additive - Roque-Borda, Cesar Augusto [UNESP]; Silva, Hanyeny Raiely Leite [UNESP]; Crusca Junior, Edson [UNESP]; Serafim, Jéssica Aparecida [UNESP]; Meneguin, Andréia Bagliotti [UNESP]; Chorilli, Marlus [UNESP]; Macedo, Wagner Costa [UNESP]; Teixeira, Silvio Rainho [UNESP]; Guastalli, Elisabete Aparecida Lopes; Soares, Nilce Maria; Blair, Jessica M.A.; Pikramenou, Zoe; et al. (Elsevier, 2021)
Microencapsulation is a potential biotechnological tool, which can overcome antimicrobial peptides (AMP) instabilities and reduce toxic side effects. Thus, this study evaluates the antibacterial activities of the Ctx(Ile21)-Ha AMP against multidrug-resistant (MDR) and non-resistant bacteria and develop and characterize peptide-loaded microparticles coated with the enteric polymers hydroxypropylmethylcellulose acetate succinate (HPMCAS) and hydroxypropylmethylcellulose phthalate (HPMCP). Ctx(Ile21)-Ha was obtained by solid phase peptide synthesis (SPPS) method, purified and characterized by HPLC and Mass Spectrometry. The peptide exhibited potent antibiotic activities against Salmonella enteritidis, Salmonella typhimurium, Pseudomonas aeruginosa (MDR), Acinetobacter baumannii (MDR), and Staphylococcus aureus (MDR). Ctx(Ile21)-Ha microencapsulation was performed by ionic gelation with high efficiency, maintaining the physical-chemical stability. Ctx(Ile21)-Ha coated-microparticles were characterized by DSC, TGA, FTIR-Raman, XRD and SEM. Hemolytic activity assay demonstrated that hemolysis was decreased up to 95% compared to single molecule. In addition, in vitro release control profile simulating different portions of gastrointestinal tract was performed and showed the microcapsules' ability to protect the peptide and release it in the intestine, aiming pathogen's location, mainly by Salmonella sp. Therefore, use of microencapsulated Ctx(Ile21)-Ha can be allowed as an antimicrobial controller in monogastric animal production as an oral feed additive (antimicrobial controller), being a valuable option for molecules with low therapeutic indexes or high hemolytic rates.
Keywords: AMP; Antibacterial activity; Microcapsules